Banda desenhada e livro ilustrado: interpretações de uma narrativa visual - Silva, Juliana Correia Soares da (2023)
This theoretical-practical project aims to present an investigation about the possibilities of relationship between text and image in illustrated books and comics to better understand the real distance between these two languages as well as how the image and the text can articulate in the visual narrative. For this, it was proposed to transform a story created by the author into a comic book and an illustrated book, and the present work, is organized around the theoretical and practical research elements, necessary for the development of this project. The research begins with a theoretical study related to the historical development of the illustrated book and comics with a focus on press and then, scholars and artists who studied the visual narrative of illustrated books and comics or used the knowledge in their projects are presented. At this point, the narrative elements present in both languages are also exposed. In the second half of the research, a report of the planning and development process in both formats of the story entitled As Aventuras Sonoras do Prúu is presented, with an exposition of the chosen methodology, how the creative process took place and the decisions taken in the narrative and in the project, that led to a comparative analysis between the two visual narratives and the conclusions resulting from this research.